IMPLEMENTASI PEMBIAYAAN MURABAHAH DALAM MENINGKATKAN PROFITABILITAS - Nizar, Muhammad (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
Product mura bah ah, is the most dominant product in use by fnancial institutions shariâah, Murabah ah is selling goods at the original price with the added advantage that is agreed between the bank with members. Cooperative financial services shari âah Arjuna in serving the fnancing of the dominant members are also using contract mura bah ah, because in addition to proft-promising, offense or supervision are also very minimal. This study is a qualitative research with a holistic approach, with the aim of knowing the implementation of fnancing mura bah ah, proftability and service systems that do KJKS Arjuna. Implementation of fnancing mura bah ah in the Cooperative Financial Services Shariâah Arjuna in accordance with the theory of murabahah, even in the last fve years the cooperative does not have diffculties or financing problems are to seize collateral. That is a guarantee that was seized because members of delinquent payments or out of the agreed rules of both or a member defaults. Most cooperative members to direct fnancing products murabah ah because of the risks faced very light compared to products mudarabah or qord ul h asa n. So the views of the percentage murabahah 60%, 20% mud Arabah, qord ul h asa n 15%, murabahah greater in the distribution of funding.Proftability at Financial Service Cooperative Shariâah Arjuna increasingly declining, this is due to the marketing system that is in the cooperative still exist, seen from the structure of the organization is still no marketing department or marketing, whereas in competition shariah business in the area Purwosari, Islamic banks or cooperative Shari âah that offer a margin of 1.2 percent just KJKS Arjuna.Keyword: Murabahah, Proftabilitas, Sharia Cooperative